2014
DOI: 10.1159/000365199
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tubular Acidosis in Sjögren's Syndrome: A Case Series

Abstract: Background: The exact frequency of distal and proximal renal tubular acidosis (RTA) in Sjögren's syndrome is unknown. Other features of Sjögren's syndrome like polyuria, glomerular manifestations, familial occurrence and pregnancy are not widely reported. The aim was to prospectively study the clinical features and outcome of distal and proximal RTA in Sjögren's syndrome and also report on other renal manifestations of Sjögren's syndrome. Methods: The present study is a prospective consecutive case series of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Interestingly, potassium levels stabilised by 31 weeks, despite infusing increasing amounts of bicarbonate. e phenomenon of rising bicarbonate requirements through gestation has not been previously described in patients with RFS, although it has been noted in other causes of renal tubular acidosis [17,18].…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, potassium levels stabilised by 31 weeks, despite infusing increasing amounts of bicarbonate. e phenomenon of rising bicarbonate requirements through gestation has not been previously described in patients with RFS, although it has been noted in other causes of renal tubular acidosis [17,18].…”
Section: Discussionmentioning
confidence: 93%
“…Although the involvement of minor salivary gland was present in all patients at the time of presentation, 62% of the patients lacked clinical signs and symptoms of salivary gland involvement. A prospective study[7] showed that RTA is a common feature of SS. In the same study, it was implicated that pSS as a cause of RTA may be missed if the oral and ocular symptoms are absent at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, only 5 out of 48 pSS patients with renal involvement were diagnosed with DI [9], and this number was 7 out of 149 patients in another prospective cohort [10]. Nephrogenic DI is usually reported to be mild [6,11].…”
Section: Discussionmentioning
confidence: 99%